2017
DOI: 10.1038/s41598-017-02941-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing Identifies Novel Pathways in Sarcoidosis Monocytes

Abstract: Sarcoidosis is a complex systemic granulomatous disorder of unknown etiology. Genome-wide association studies have not been able to explain a causative role for nucleotide variation in its pathogenesis. The goal of the present study was to identify the gene expression profile and the cellular pathways altered in sarcoidosis monocytes via RNA-sequencing. Peripheral blood monocytes play a role in sarcoidosis inflammation. Therefore, we determined and compared the transcriptional signature of monocytes from perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 55 publications
(63 reference statements)
4
30
0
1
Order By: Relevance
“…We showed that predominant biological processes associated with the differential mRNA gene expression of BALf cells were upregulation of neutrophil function in IPF and lymphocyte function in sarcoidosis. 14 We obtained contrary results where expression of mRNA of ribosome related proteins was upregulated. Clusters formed by genes with changed mRNA expression in IPF samples were implicated in the processes of cell adhesion and T A B L E 2 The most significantly regulated microarray probes: probes with differences of the highest statistical significance as well as the highest and the lowest induced expression for the comparison of IPF vs sarcoidosis BALf cells migration, metalloproteinase expression and negative regulation of cell proliferation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We showed that predominant biological processes associated with the differential mRNA gene expression of BALf cells were upregulation of neutrophil function in IPF and lymphocyte function in sarcoidosis. 14 We obtained contrary results where expression of mRNA of ribosome related proteins was upregulated. Clusters formed by genes with changed mRNA expression in IPF samples were implicated in the processes of cell adhesion and T A B L E 2 The most significantly regulated microarray probes: probes with differences of the highest statistical significance as well as the highest and the lowest induced expression for the comparison of IPF vs sarcoidosis BALf cells migration, metalloproteinase expression and negative regulation of cell proliferation.…”
Section: Discussionmentioning
confidence: 70%
“…13 The significant changes in ribosomal proteins in sarcoidosis were described earlier by Tarleja et al These authors showed that 62 genes related to ribosome were significantly downregulated in blood monocytes of patients with sarcoidosis compared to healthy controls. 14 We obtained contrary results where expression of mRNA of ribosome related proteins was upregulated. The differences may be F I G U R E 1 Hierarchical clustering and heat map based on the mRNA expression of 60 genes with the lowest P-value in the comparison of patients with IPF and sarcoidosis related to different comparative groups (healthy controls vs. IPF patients in our study) as well as to different cells analysed in both studies (blood monocytes vs. BALf cell in our study), in particular in the context of a known discordance between circulating and pulmonary immune responses in sarcoidosis.…”
Section: Probe Identifier Gene P-value Adjusted P-value Fold Changementioning
confidence: 70%
“…RNA-sequencing analysis of monocytes of sarcoidosis patients revealed several differentially expressed genes, with enrichment of ribosome, phagocytosis, lysosome, proteasome, oxidative phosphorylation, and metabolic pathways are the main pathways ( 187 ). No epigenetic analysis of monocytes in sarcoidosis has been done so far ( 188 ).…”
Section: Sarcoidosismentioning
confidence: 99%
“…Interesting approaches were to compare the transcriptome of self-limiting versus progressive lung sarcoidosis with fibrotic evolution, to search for sarcoidosis-specific gene signatures compared with tuberculosis, an infectious disease also characterized by granuloma, and/or to identify transcriptome signatures related to disease outcome [129]. A recent study focused on the transcriptional signature in monocytes from sarcoidosis patients and healthy controls by an RNA-sequencing screening of the poly-adenylated (or purified mRNA) fraction of RNA [130]. Among 2446 genes significantly differentially expressed in monocytes between sarcoidosis and controls, the authors identified a downregulation of genes involved in proteasome degradation and ribosomal pathways, and conversely, an upregulation of genes, such as, for example, ATP6AP1 (ATPase H + transporting accessory protein 1), CYBB (cytochrome b-245 beta chain), LAMP2 (lysosomal-associated membrane protein), PLK1 (serine/threonine-protein kinase or polo-kinase 1), and SERPINA1 (serpin family A member 1, encoding alpha-1 antitrypsin), implicated in phagocytosis and lysosomal pathways.…”
Section: A Functional Link Between Genomic and Transcriptome Analysismentioning
confidence: 99%